2019
DOI: 10.1016/j.bjoms.2019.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, timing, presentation, treatment, and outcomes of second primary head and neck squamous cell carcinoma after oral cancer

Abstract: Patients following their initial presentation of oral squamous cell carcinoma (SCC) have a lifelong risk of another new head and neck SCC. The present study aimed to establish the rates of second primary (SP), baseline characteristics (site, clinical or pathological stage, smoking and alcohol history), timing, presentation, treatment and outcomes. From the regional unit, records of patients treated with curative intent for their first oral cancer between 2002 and 2007 inclusive were analysed. Patients had at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…This was particularly evident in the oral cavity. A recurrence in the oral cavity after an oral index tumor has been previously reported also by Rogers et al [31], and could be explained with a strong local effect of carcinogens in this area.…”
Section: Discussionsupporting
confidence: 66%
“…This was particularly evident in the oral cavity. A recurrence in the oral cavity after an oral index tumor has been previously reported also by Rogers et al [31], and could be explained with a strong local effect of carcinogens in this area.…”
Section: Discussionsupporting
confidence: 66%
“…This may be due to the different risk factors between HPV‐related and HPV‐unrelated cancer; HPV‐related HNSCCs are not associated to alcohol abuse and smoking history, the most important risk factors for the development of SPT (Boakye et al., 2018). Several studies reported that early stage of the index cancer (i.e., absence of nodal involvement) was a risk factor associated with the development of SPT, reflecting survivorship (Lee et al., 2013; Rogers et al., 2019). We collected data about stage, nodal involvement, and grading and of primary tumor, but we did not find significant correlation with development of SPT.…”
Section: Discussionmentioning
confidence: 99%
“…HDR has the advantage of high dose radiation at the target area sparing the remaining tissues, thereby minimizing post radiation sequelae and enhancing the quality of life. [1][2][3][4][5]12,13 Since the radiation implant was placed after the accurate seating of the mold at each radiotherapy session, it was an afterload brachytherapy mold. 13 This minimized the risk of radiation exposure to the patient and to the personnel handling the mold.…”
Section: Discussionmentioning
confidence: 99%
“…Metachronous second primary carcinoma (MCSPC) are tumors occurring in areas close to the region of primary carcinoma, which have been detected 6 months or more after the index carcinoma is treated. [1][2][3][4][5] High dose rate (HDR) brachytherapy is preferred for local tumor control and to conserve form and function in treatment of MCSPC. [6][7][8][9] A brachytherapy mold is used to carry the radioisotope as radiation source.…”
Section: Introductionmentioning
confidence: 99%